Improvement in the reliability of crystalline silicon solar cell interconnection by using Nickel Micro-Plating Bonding (NMPB) technology. (1st January 2023) - Yu, Xinguang; Fu, Zhi; Morisako, Isamu; Koshiba, Keiko; Iizuka, Tomonori; Tatsumi, Kohei
Abstract: It is popular to research promoting the light conversion efficiency of crystalline silicon solar cell photovoltaic (PV) modules. However, excellent light conversion efficiency does not mean it could maintain initial performance after long-term running. Long-term reliability of interconnection to assemble crystalline silicon solar cells in PV modules is critical to ensure that the device performs continually for up to 20 years. It is reported that most crystalline PV modules fail from corrosion and breakage of the interconnector with the solder joint. As a result, improvement of interconnection technology is highly necessary. Nickel (Ni) Micro-Plating Bonding (NMPB) is an innovative interconnection technology for crystalline silicon solar cells: copper ribbons bonded with lead or lead-free solder are replaced by copper wires bonded with Ni electroplating film. The NMPB interconnection provides key advantages: low temperature (55 °C) process, enhancement of reliability from strain and stress caused by high temperature, and coefficient of thermal expansion (CTE) mismatch between metal and silicon. Furthermore, the material of NMPB, Ni, possesses excellent corrosion resistance. High reliability was confirmed with about 1.9% degradation of output power for up to 1000 thermal cycling tests and 3.8% for 1000 h of damp heat tests in bare NMPB solar cells, while 64.7% degradation in thermal cycling tests and 23.0% in damp heat tests were confirmed in solder bonding solder cells.